1982
DOI: 10.1111/j.1532-5415.1982.tb05060.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Admission or Nonadmission of the Aged to the Hospital

Abstract: A prospective study was carried out to determine which social, functional, or medical factors influenced the decision to admit or not to admit aged people to a general hospital in Israel. The study also focused on characteristics of patients admitted to the geriatric ward of the medical division as distinct from those sent to the internal medicine ward. Two hundred patients over the age of 65 were examined during ten consecutive intake days for the internal medicine ward over a period of five weeks. One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Only 17 of the 111 others (15%) were referred for geriatric medical review during the hospitalisation (intervention 6, control 11). Seventy-four patients (67%) were referred to a physiotherapist (intervention 36, control 38), 63 (57%) to a social worker (intervention 32, control 31), 52 (47%) to an occupational therapist (intervention 27, control Number referred to nurse for assessment 25), and 20 (18%) were not referred (intervention 9, control 11). Boxes 3, 4 and 5 show the significant predictors for each of the three outcome measures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 17 of the 111 others (15%) were referred for geriatric medical review during the hospitalisation (intervention 6, control 11). Seventy-four patients (67%) were referred to a physiotherapist (intervention 36, control 38), 63 (57%) to a social worker (intervention 32, control 31), 52 (47%) to an occupational therapist (intervention 27, control Number referred to nurse for assessment 25), and 20 (18%) were not referred (intervention 9, control 11). Boxes 3, 4 and 5 show the significant predictors for each of the three outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies consistently report impaired function to be a strong predictor of outcomes, including admission status, 25 LOS 4 and functional decline. 26 In concordance, the Waterlow scale was a significant predictor of all three outcomes in our multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies report associations between disability and LOS for selected diagnoses, or in cohorts undergoing rehabilitation rather than general patients in the internal medicine wards. [14][15][16] For example, Bohannon and Cooper demonstrated that LOS and function at discharge were influenced favourably by a higher level of function on admission in selected stroke patients. 14 Also, Greenberg et al observed that geriatric patients, who were more disabled, had longer LOS compared to general medicine patients.…”
Section: Introductionmentioning
confidence: 99%
“…14 Also, Greenberg et al observed that geriatric patients, who were more disabled, had longer LOS compared to general medicine patients. 15 The purpose of this study was to evaluate the relationships between disability as measured with the Functional Independence Measure (FIM) at discharge and LOS in internal medicine patients. This is essential, as Internal Medicine (IM) patients often form the largest cohort of patients in a tertiary general hospital, including all the public hospitals in our country.…”
Section: Introductionmentioning
confidence: 99%